2012
DOI: 10.3856/vol40-issue4-fulltext-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress proteins and auxiliary anti stress compounds in intertidal macroalgae

Abstract: ABSTRACT. Intertidal macroalgae are exposed to strong variation in the physical environment and thus, diverse anti-stress mechanisms are displayed by these organisms. Stress proteins (also called heat shock proteins, HSPs) have been invoked as potential protective mechanism, especially during stressful action of temperature and solar radiation. Therefore, macroalgae have not normally been used as model organisms in studies of these molecules. The present study compiles the existing information from intertidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
0
12
0
3
Order By: Relevance
“…Likewise, in the genus Ulva , the carbon‐assimilation pathways also could play an important role in its acclimation to different light conditions (Cruces et al. 2012b, Gómez and Huovinen , Holzinger et al. , Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the genus Ulva , the carbon‐assimilation pathways also could play an important role in its acclimation to different light conditions (Cruces et al. 2012b, Gómez and Huovinen , Holzinger et al. , Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…The acclimation of the photosynthetic apparatus to diurnal changes of light in Ulva are related to the efficiency of a series of mechanisms such as: (i) the dissipation of energy as heat via the xanthophyll cycle (Franklin et al 2003, Mou et al 2013), (ii) a reduction in the efficiency of energy transfer to PSII reaction centers (i.e., photoinhibition; Pescheck et al 2016), and (iii) changes in the size of the light-harvesting antennae through the reduction of photosynthetic and accessory pigments (Melis 2009). Likewise, in the genus Ulva, the carbon-assimilation pathways also could play an important role in its acclimation to different light conditions (Cruces et al 2012b, G omez and Huovinen 2012, Holzinger et al 2015, Zhao et al 2016. For example, studies have shown that the exposure of U. prolifera to light intensities >1,000 lmol photons Á m À2 Á s À1 triggered a decrease in the gene expression of key enzymes of C 4 metabolism and RuBisCO's large subunit (Xu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…O estudo de Zou et al (2017) reportou para S. polycystum Agardh tolerância a diferentes condições de temperatura ( A macroalga verde Ulva prolifera Müller, quando analisada a diferentes temperaturas (5,10,15,20,25,30, 35 e 40 °C) após 3, 6 e 24 h, apresentou indução de proteínas de choque térmico (HSP; Heat Shock Protein) sob temperaturas de 5 e 15 °C e em altas temperaturas acima de 30 °C . Cruces et al (2012) ex. aminoácidos tipo micosporinas, substâncias fenólicas, poliaminas, entre outras) (Cruces et al, 2012).…”
Section: I2 Efeito Da Temperatura Nas Macroalgas Marinhasunclassified
“…Cruces et al (2012) ex. aminoácidos tipo micosporinas, substâncias fenólicas, poliaminas, entre outras) (Cruces et al, 2012).…”
Section: I2 Efeito Da Temperatura Nas Macroalgas Marinhasunclassified
“…Seaweeds are also capable to produce chemical compounds in response to various environmental stresses such as e.g. mycosporine-like amino acids (MAAs), phenolic compounds, polyamines, and stress proteins Hoyer et al, 2001;Houvinen et al, 2004;Cruces et al, 2012). The efficiency to absorb-dissipate energy and the acclimation responses to fluctuating environmental factors, reflect a wide range of adaptive abilities and tolerances in macroalga species across their range of distribution.…”
Section: Potential Of Porphyra As Local Resourcesmentioning
confidence: 99%